Ordinal Logistic Regression Approach for Probability Analysis of Student Stress Levels - Khikmah, Laelatul; Ratnasari, Elis Meida (Universitas Muhammadiyah Semarang Press, 2022)
Stress is a condition or condition where a person feels pressured because of the many demands, both from within and from outside the individual that must be met. Stress is an uncomfortable stressful event for someone that can cause negative effects such as dizziness, emotional instability, irritability, loss of appetite, difficulty concentrating, and difficulty sleeping. One of the factors that cause stress is doing the Final Project. Someone who is experiencing stress can be seen from the level of stress, namely the level of mild, moderate and severe stress. To see a person's stress level, several variables can be used, namely physiological, emotional, cognitive, supervisory, and knowledge variables. This study aims to find out what variables affect stress levels in students. The analysis used is Ordinal Logistic Regression analysis which is one of the statistical analyzes used to determine the probability of events that are affected by the independent variable, where the response variable is a categorical scale. Variables that affect stress levels are emotional, cognitive and knowledge variables. The results showed that the higher a person's emotion, cognitive and knowledge, the smaller the chance for someone to experience severe levels of stress.